Pengaruh Algoritma TikTok terhadap Pola Konsumsi Konten Generasi Z di Indonesia: Studi Analisis Perilaku dan Strategi Engagement - Anindya Saraswati Putri; Bayu Ramadhan Prakoso (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
TikTok, one of the most popular platforms, has earned Generation Z's affection in Indonesia. Through personalization, the app's intelligent algorithms force its users to consume content and interact. Even though such algorithms contain elements that may influence user consumption and interaction, the research done locally on the subject is rather scarce. A major concern in this study is how the TikTok algorithm impacts content consumption and engagement strategies used by Generation Z in Indonesia. The study followed a quantitative survey method among purposively sampled 450 active TikTok users of Generation Z. The data collection involved an online Likert scale questionnaire, which was processed through multiple linear regression analysis. It was found that the TikTok algorithm does affect patterns of content consumption significantly (β = 0.512; R² = 0.262) and engagement strategies (β = 0.431; R² = 0.186). 78.4% of respondents used the For You page to discover various content within the entertainment category (67.3%) as a prime focus, followed by light education (45.8%) and those that show viral trends (42.7%). The study ends up entering the literature by trying to put together technical algorithm analysis with behavioral analysis of digital consumption in the case of Indonesia's generation Z, thereby enriching the literature in algorithmic media theory. While most users engage with the content by liking videos (85.1%), fewer users share videos (39.6%): the fact is that users mostly engaged in the study using only one interaction form. An example of these practical implications is how the platform developers, marketers, and policy-makers will set about optimizing retention strategy and creating engagement with millennial or young users.